Strategies of acts and morals teachers in preventing sexual violence in man temanggung - Luk Luki Fitri Rohmatilah; Karisma Rizqi Lestari; Adi masna; Dwi Indah Rahmawati; Choirina Amma Miftachurrahmah; Umi Koyimah; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2025)
The background of this research is the importance of dressing according to Islamic law, not only as a religious obligation, but also as a form of self-protection to reduce the risk of harassment and sexual violence. Data from the National Commission on Violence Against Women shows that cases of sexual violence in Indonesia are still very high and a serious concern. Aqidah Akhlak Education has strategic potential in shaping students' character and awareness to protect themselves, particularly through the material on Dress Etiquette. This study aims to describe the strategies used by Aqidah Akhlak Teachers in preventing sexual violence at MAN Temanggung, as well as the obstacles and solutions faced. The research method used was qualitative with a phenomenological approach. Data collection techniques included observation, interviews, and documentation. The results showed that teachers implemented affective, expository, and cooperative learning strategies. In addition, collaboration with BK Teachers and parents is an important part of the prevention process. Obstacles faced are the cultural taboo of discussing sexual issues, minimal student awareness, and the influence of social media. These strategies are strengthened by the role of the school environment, enforcement of discipline, and communication with students' guardians.